A universe of dwarfs and giants: genome size and chromosome evolution in the monocot family Melanthiaceae. Issue 4 (2nd December 2013) - Pellicer, Jaume; Kelly, Laura J.; Leitch, Ilia J.; Zomlefer, Wendy B.; Fay, Michael F.
Summary: Since the occurrence of giant genomes in angiosperms is restricted to just a few lineages, identifying where shifts towards genome obesity have occurred is essential for understanding the evolutionary mechanisms triggering this process. Genome sizes were assessed using flow cytometry in 79 species and new chromosome numbers were obtained. Phylogenetically based statistical methods were applied to infer ancestral character reconstructions of chromosome numbers and nuclear DNA contents. Melanthiaceae are the most diverse family in terms of genome size, with C‐values ranging more than 230‐fold. Our data confirmed that giant genomes are restricted to tribe Parideae, with most extant species in the family characterized by small genomes. Ancestral genome size reconstruction revealed that the most recent common ancestor (MRCA) for the family had a relatively small genome (1C = 5.37 pg). Chromosome losses and polyploidy are recovered as the main evolutionary mechanisms generating chromosome number change. Genome evolution in Melanthiaceae has been characterized by a trend towards genome size reduction, with just one episode of dramatic DNA accumulation in Parideae. Such extreme contrasting profiles of genome size evolution illustrate the key role of transposable elements and chromosome rearrangements in driving the evolution of plant genomes.